PENGARUH MODEL ROUNDTABLE TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA KELAS IV SDN LESANPURO 1 - Dyah Kurniastuty, Syarifah Al Kamilah (PRIMARY EDUCATION JOURNAL (PEJ), 2024)
One of the important language skills is the ability to write. One of the problems faced by students in grade IV of SDN Lesanpuro 1 is poor writing skills in procedure texts. This is due to the disorganization of the writing activity process between Pre-Moment and Post, which causes students to not understand the flow of their writing skills. In addition, teachers still tend to dominate the learning models and approaches used, which results in less than optimal learning outcomes. This study aims to determine students' writing ability in writing procedure texts in grade IV of SDN Lesanpuro 1 Malang and to find out how the use of the roundtable model impacts their ability. This study used a quantitative approach. The type of research was pre-experimental, and the research design was one group pretest posttest design. The sample size was 28 students, and the sampling technique was saturated sampling. There were three steps taken to collect data: saturated sampling, observation, and documentation. The results of the Wilcoxon Signed Rank Test, which was conducted using the JASP computer program, showed a p value of 0.001, indicating that the roundtab model had a significant positive effect.